DEFORMATION HISTORY OF THE BLUESCHIST-FACIES SEQUENCES FROM THE VILLA DE CURA UNIT (NORTHERN VENEZUELA) - Ellero, Alessandro; Marroni, Michele; Padoa, Elisa; Pandolfi, Luca; Urbani, Franco (Ofioliti, 2001)
The Serrania del Interior terrane is located in Northern Venezuela, that represents the southern margin of the Caribbean plate. This terrane includes the Villa de Cura unit, which mainly consists of multiple sub-units of metamorphosed and deformed Cretaceous volcano-sedimentary sequences. These sequences are commonly interpreted as generated in a supra-subduction zone setting.The structural history of the Villa de Cura blueschists-facies units includes four main deformational phases, from D1 to D4. The first D1 phase is mainly represented by a relict S1 schistosity developed under HP/LT conditions. The relic S1 schistosity is deformed by isoclinal to subisoclinal F2 folds showing similar geometry. The F2 folds are characterized by a continuous S2 crenulation cleavage developed under greenschist-facies metamorphism. The parallelism between the A2 axes and the related L2 mineral lineations suggests an interpretation of the F2 folds as sheath folds developed during non-coaxial deformation. The kinematic indicators suggest a top-to-W sense of shear for the D2 phase. The D3 phase is distinguished by asymmetric, parallel F3 folds with a S vergence. Finally, the D4 phase consists of F4 open, gentle folds with high-angle to sub-vertical axial planes.The collected data suggest a complex deformation history, characterized by coupling of strike-slip tectonics and shortening during the retrograde evolution of the blueschist-facies sequences.